Risk warning landslide In the mountainous districts of Quang Ngai province - Hùng, Phạm Văn; Dũng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2014)
On the basis of studies to assess the status and impact factors arising landslides, partitioning allows warned the risk of landslides in the mountainous districts of Quang Ngai province. - On the mountainous province of Quang Ngai distributed sliding block 809, they form bands running under the sublatitude, sublongtitude and the NE-SW with sliding mass density reached 10-12 block/10km2. - Landslides occur due to 11 impact factors arising, including slope and slope factor mean annual rainfall plays a key role; followed by the crust of factors, geology, tropical impact fracture dynamics, hydrogeology, fracture density, the density of deep separation, horizontal separation density, cover plant phue and traffic density. Zoning map warning the risk of landslides in mountainous districts of Quang Ngai province was built on the basis of the integrated 11 Landslide hazard maps in spatial analysis component in a GIS environment. - On the mountainous districts of Quang Ngai province, the average risk of landslides accounted for 40.67% of the research natural area, distributed in the districts of Ba To, Son Ha, Tay Tra. Areas at risk of landslides in high level accounting for 24.32% of the natural areas of the study area, mainly distributed in the districts of Ba To, Son Ha and Tra Bong. Areas at risk of landslides in low-level accounting for 20.28% of the area of research natural areas, distributed in the district: Ba To, Son Ha and Son Tay, partly in Tay Tra district, Minh Long and Tra Bong. Areas with high risk of landslides accounted for only 0.58% of the natural area and research area is mainly distributed in Tra Bong district and scattered in Ba To, Son Ha. Areas with very low risk of landslides accounted for 14.15% of the research natural area, distributed in the districts of Shon Tay, Ba To and scattered in the districts of Son Ha, Tay Tra and Minh Long.